Improving damage resistance and load capacity of thin-ply laminates using ply clustering and small mismatch angles. (February 2019) - Wagih, A.; Maimí, P.; Blanco, N.; García-Rodríguez, S.M.; Guillamet, G.; Issac, R.P.; Turon, A.; Costa, J.
Abstract: Thin-ply composite laminates are currently receiving researchers' attention due to their specific advantages in delaying or even suppressing some damage mechanisms such as matrix cracks. Lower load capacity during impact event is one of the main factors against thin-ply laminates use. This paper presents novel thin-ply laminate design with improved damage resistance and load capacity. First, the effect of mismatch angle on damage resistance and damage mechanisms occurring during an impact event on thin-ply composite laminates is studied by means of a series of quasi-static indentation tests and X-ray computed tomography and ultrasonic C-scan techniques. The results show that the projected delamination area in thin-ply laminates is independent of the mismatch angle. However, the different damage mechanisms and load capacity are dependent on the mismatch angle; the smaller the mismatch angle is, the higher the matrix cracking density, the lower number of delaminated interfaces, the higher fiber breakage density and higher load capacity are. Based on these results and other available in the literature, a thin-ply laminate with small mismatch angles between plies (to improve the maximum load) and clustered plies in the upper part of the laminate (to force damage growth in this part) is designed to present improved damage resistance and load capacity of thin-ply laminates. This laminate shows 38.8% lower delamination area when compared to the laminate with small mismatch angles.